Diagnostic Accuracy of Digital Phosphor Plates Using Pseudo-Color Enhancement for Detection of Horizontal Root Fractures in Single-Rooted Teeth - Sandra Mehralizadeh; Sahar Mohammadi; Ahmadreza Talaeepour; Peaiman Mehrvarzfar; Maryam Mirzaee (Islamic Dental Association of Iran, 2014)
Background and Aim : If root fractures remain undetected, pulp necrosis will occur in 25% of cases leading to eventual tooth loss. The purpose of this study was to evaluate the diagnostic accuracy of digital phosphor plates using pseudo-color enhancement for detection of horizontal root fractures in single-rooted teeth .   Materials and Methods : Eighty-two human single-rooted teeth were evaluated (41 with no horizontal fracture and 41 with horizontal fractures). Digital intraoral imaging plate system.   (Digora® Optime PSP System, Soredex) was used to obtain 16-bit gray scale images. Five 16-bit images were obtained from each specimen and saved (one original and four with pseudo-color enhancement). Four observers evaluated the images twice with a 2-week interval. Accuracy, positive predictive value (PPV), negative predictive value (NPV), specificity and sensitivity for each observer and each image group were calculated .   Results : The diagnostic sensitivities were not significantly different among the five images (p absolute=0.125 , p complete=0.170). But, statistically significant differences were found in the diagnostic specificity (p absolute=0.019, p complete=0.016) among the five views. Cool and Summer views had higher diagnostic specificity than Bone, Copper and Original views (p=0.025). Kappa and Weighted Kappa values showed statistically significant differences for intra- and inter-observer reliability in the five views (p=0.032).   Conclusion : Both Cool and Summer views were suitable for detection of horizontal root fractures and had statistically significant differences with the original view .